Public health and prevention: acting to make longer lives healthier. Issue 2 (13th June 2016) - Alessi, Charles; Rashbrook, Elaine
Abstract : Purpose: – The purpose of this paper is to outline the action that can be taken to ensure longer and healthier lives. Design/methodology/approach: – The paper draws on the relevant recommendations set out by the National Institute for Clinical Excellence to delay or prevent the onset of ill health in later years, followed by a number of recommended approaches to promote healthy behaviours in older adults as well as those in midlife. Findings: – There is a clear need for public health and the prevention agenda to help ensure that later years are not just longer, but healthier. Practical implications: – The paper identifies how, when and where the health risks associated with the majority of years lost to ill health can be addressed, and advocates the importance of taking an asset-based approach to promoting good health in older people. Originality/value: – The paper is a comprehensive review of the key public health actions that can be taken to ensure longer and healthier lives.